Comparative Study on Pollutant Carrying Capacity of Plain Sluice-controlled River under Different Water Diversion Scale - YU Ting; CHEN Yanfei; ZHOU Chi; WU Xuejie; ZHANG Xiulian; CHEN Yunmei; CHEN Xiaoqun (Renmin Zhujiang)
Water pollutant carrying capacity refers to the maximum allowable pollutant carrying capacity in water body on the basis of meeting the water environmental quality standard of water function area.The calculation of pollutant carrying capacity is of great practical significance to the rational development & utilization and effective protection of water resources.Water conservancy projects such as sluice gates in rivers and lakes will change the hydrological process of rivers and lakes,thus affecting the pollutant carrying capacity of rivers and lakes.Taking the Tongshun River,a typical sluice-controlled river seriously disturbed by human beings,as the research object,this paper analyzes the pollutant carrying capacity of the main stream of Tongshun River under three conditions,namely 10 m3/s,13 m3/s and 15 m3/s,of the intake flow of Zekou sluice by the model method and pollution load method.The results show that different diversion scales have different effects on the pollutant carrying capacity of sluice-controlled river,and there is no complete positive correlation under the restriction of multiple parameters.With the continuous progress of water pollution control projects,the larger the scale of river diversion,the smaller the amount of pollutants need to be reduced.The calculation scheme presented in this paper can provide the basis for the establishment of scientific and feasible sluice dam regulation rules in Tongshun River,and also offer countermeasures and measures for river regulation.